Delirium in intensive care: A stepped-wedge cluster randomised controlled trial for a nurse-led intervention to reduce the incidence and duration of delirium among adults admitted to the intensive care unit (protocol). Issue 5 (September 2020) - Lynch, Joan; Rolls, Kaye; Hou, Yu Chin; Hedges, Sonja; Al Sayfe, Masar; Shunker, Sharon-Ann; Brennan, Kathleen; Sanchez, David; Bogdanovski, Tony; Hunt, Leanne; Alexandrou, Evan; Frost, Steven A.
Abstract: Background: Delirium is an acute disorder of attention and cognition with the highest rates among adults receiving intensive care. An acute episode of delirium is associated with morbidity and mortality, as well as a significant psychological sequela. Importantly, an increasing body of evidence supports the benefit of nonpharmacological, nurse-led interventions to reduce the incidence and duration of delirium among adults cared for in the intensive care unit (ICU). Objectives: This study will evaluate the impact of a nursing-led delirium prevention protocol that is aimed at reducing the incidence and duration of delirium among adults admitted to the ICU. The delirium prevention nursing protocol specifically targets risk factors for delirium. Study plan: A stepped-wedge cluster randomised controlled trial approach will be used to assess the effectiveness of the nurse-led intervention, in four adult ICUs across the South Western Sydney Local Health District (SWS-LHD), over a 12-month period. The primary outcomes of interest are (i) the incidence of delirium before and after the implementation of the nurse-led intervention and (ii) the number of delirium-free days during an ICU stay, before and after the implementation of the nurse-led intervention. Trial registration: Australian New Zealand Clinical Trials Registry (ANZCTR): (ACTRN12618000411246p)